2017
DOI: 10.1002/jbio.201700019
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering analysis of urine from deceased donors as a prognostic tool for kidney transplant outcome

Abstract: We report the utility of surface-enhanced Raman scattering (SERS) analysis of urine from deceased donors for prognosis of kidney transplant outcomes. Iodide-modified silver nanoparticles were used as the enabler for sensitive measurements of urine proteins. Principal component analysis (PCA) and linear discriminant analysis (LDA) were employed for the statistical analysis of the SERS data. Thirty urine samples in three classes were analysed. The ATN class consists of donors whose kidneys had acute tubular necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Furthermore, Raman spectroscopy has shown promise in prognosticating renal allograft outcome from the urine of deceased donors. 27 Using silver nanoparticles for surface-enhanced Raman spectroscopy of deceased donor urine, Chi et al. 27 achieved a sensitivity of 91% for identifying donor kidneys with acute tubular necrosis but ultimately good allograft function, as compared with allografts that ultimately displayed delayed graft function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Raman spectroscopy has shown promise in prognosticating renal allograft outcome from the urine of deceased donors. 27 Using silver nanoparticles for surface-enhanced Raman spectroscopy of deceased donor urine, Chi et al. 27 achieved a sensitivity of 91% for identifying donor kidneys with acute tubular necrosis but ultimately good allograft function, as compared with allografts that ultimately displayed delayed graft function.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Using silver nanoparticles for surface-enhanced Raman spectroscopy of deceased donor urine, Chi et al. 27 achieved a sensitivity of 91% for identifying donor kidneys with acute tubular necrosis but ultimately good allograft function, as compared with allografts that ultimately displayed delayed graft function. In addition, in a preliminary study of renal allograft recipients, silver nanoparticle-enhanced spectra obtained from urine samples collected 1 day after surgery identified allografts at risk for future dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged treatment of AgNPs also led to the activation of cell proliferative, survival and proinflammatory factors (Akt/mTOR, JNK/Stat and Erk/ NF-κB pathways and IL1β, MIP2, IFN-γ, TNF-α and RANTES) and dysfunction of normal apoptotic pathway [42]. Iodide-modified silver nanoparticles were used as the enabler for sensitive measurements of urine proteins [43]. These assist in identification of high-risk AKI type based on common urinary biomarkers [43].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Iodide-modified silver nanoparticles were used as the enabler for sensitive measurements of urine proteins [43]. These assist in identification of high-risk AKI type based on common urinary biomarkers [43]. AgNPs may have potential to adversely affect the kidney functions as well as capability to cause myriad of cellular damage [44].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…In the kidney transplant recipients, Raman spectrum was used for hydroxyethyl starch detection at 3 months after transplantation . In addition, surface‐enhanced Raman scattering was reported that provided the subtle changes in urine of kidney donors, which showed high correlation with delayed graft function and acute tubular necrosis in kidney transplant recipients . The determination of creatinine, urea and glucose by Raman spectrum in urine was also used for renal impairment assessment in patients with diabetes and hypertension .…”
Section: Introductionmentioning
confidence: 99%